Transmission risk of severe acute respiratory coronavirus virus 2 (SARS-CoV-2) to healthcare personnel following unanticipated exposure to aerosol-generating procedures: Experience from epidemiologic investigations at an academic medical center. (2nd February 2023) - Fawcett, Sharon E.; Madhusudhan, Meghan S.; Gaddam, Emily N.; Almario, Matthew J.; Masih, Shawna R.; Klute-Evans, Dee Dee; Johnson, Julie C.; Stroud, Clarise D.; Dolan-Caren, Judy A.; Ben-Aderet, Michael A.; Luria, Jeffery; Morgan, Margie A.; et al.
Abstract: Healthcare personnel (HCP) with unprotected exposures to aerosol-generating procedures (AGPs) on patients with coronavirus disease 2019 (COVID-19) are at risk of infection with severe acute respiratory coronavirus virus 2 (SARS-CoV-2). A retrospective review at an academic medical center demonstrated an infection rate of <1% among HCP involved in AGPs without a respirator and/or eye protection.